Barriers to FSC certification for small forest owners in Sweden - Johansson, Cristopher (SLU/Dept. of Forest Products, 2018)
The awareness of sustainable development challenges is growing. Companies are important players in society's development and in order to follow that development, action towards more sustainable business practises is required. Forests are important to the environment, and the forestry industry is largely influenced by society's demands for social, environmental and economic sustainability. In order to strengthen the reliability of sustainability efforts, many forest owners join environmental certification organizations to get their forests certified. The purpose of forest certification is to create a reliable link between consumer and forest product, that proves the product is produced responsibly in terms of social and environmental aspects. The most commonly used certifications in Sweden are Forest Stewardship Council (FSC) and the Program for Endorcement of Forest Certification (PEFC).